1982
DOI: 10.1177/0145482x8207600602
|View full text |Cite
|
Sign up to set email alerts
|

Mental Processes Mediating Independent Travel: Implications for Orientation and Mobility

Abstract: Despite advances in the professional areas of orientation and mobility, processes of spatial learning and orientation are not well understood, and the benefits of existing teaching techniques vary widely from client to client. Wayfinding is mediated by mental processes through which travelers learn the spatial layout of a locale, update their own positions relative to their surroundings, and apply general spatial concepts to particular travel situations. In this article we describe these three components, desc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
28
1
1

Year Published

1987
1987
2020
2020

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 73 publications
(30 citation statements)
references
References 10 publications
0
28
1
1
Order By: Relevance
“…It seems reasonable to assume that reliance on such heuristics will be greater, the less spatial information is available from more direct sources. This assumption is supported by the finding of greater heuristic influence in visual memory than perception of an explicitly present display (Thorndyke, 1981;Tversky, 1981), in touch as compared with vision (Lederman & Taylor, 1969), and in visually inexperienced relative to sighted, blindfolded observers (Rieser, Guth, & Hill, 1982). Lederman et al (1985) identified two types of heuristics used to determine spatial parameters of small two-dimensional pathways that were explored manually.…”
mentioning
confidence: 94%
“…It seems reasonable to assume that reliance on such heuristics will be greater, the less spatial information is available from more direct sources. This assumption is supported by the finding of greater heuristic influence in visual memory than perception of an explicitly present display (Thorndyke, 1981;Tversky, 1981), in touch as compared with vision (Lederman & Taylor, 1969), and in visually inexperienced relative to sighted, blindfolded observers (Rieser, Guth, & Hill, 1982). Lederman et al (1985) identified two types of heuristics used to determine spatial parameters of small two-dimensional pathways that were explored manually.…”
mentioning
confidence: 94%
“…ment is required Juurmaa, 1973 . It is also clear from studies on the microgenetic development of cognitive maps of particular novel areas in blind and visually impaired adults that blind and visually impaired people use different and often less effective means for processing spatial information ŽMillar, 1982ŽMillar, , 1988ŽMillar, , 1994Rieser et al, 1982Rieser et al, , 1986 . Ungar et al, 1996b .…”
Section: Introductionmentioning
confidence: 99%
“…Manning, Lew, Li, Sekuler, & Kahana (2014) were able to predict taxi driver's behaviour by controlling for two parameters, namely, vision (V) and memory (M) where the M parameter establishes a limit to the amount of time that a particular piece of information remains stored in the system cognitive-map. Without the continuous flow of information that vision provides, it is very tough to build and maintain cognitive maps (Rieser, Guth, & Hill, 1982;Golledge, Klatzky, & Loomis, 1996). Nonetheless, studies from both cognition and robotics proved that concepts developed in spatial cognition are sound enough to be valid regardless input modalities (Chown & Yeap, 2015).…”
Section: Key Pointsmentioning
confidence: 99%
“…The main limitations of blind people's most informative sensing modalities come from their short range, their discontinuous information flow, and their sequential nature (Cattaneo et al, 2008;Golledge, Klatzky, & Loomis, 1996;Rieser, Guth, & Hill, 1982). The latter one is hard to address.…”
Section: Key Pointsmentioning
confidence: 99%
See 1 more Smart Citation